Wind Power: Current State and Perspectives - Linnik, Vladimir Yu.; Voronova, E. Yu.; Pavlyuk, Larisa V.; Zich, Alexey (International Journal of Energy Economics and Policy, 2020)
Due to the depletion of resources for traditional energy, as well as due to the gradual abandonment of nuclear power in a number of countries, the world pays great attention to energy conservation and energy efficiency, one of the main sources of which is renewable energy, which includes wind energy. Wind power is the most developed renewable energy industry (excluding hydro), which affects its economic characteristics. Thus, onshore wind power plants are characterized by one of the lowest indicators of the cost of electricity production among alternative types of generation. However, offshore wind power plants are still inferior to some types of renewable energy sources and are twice the level of traditional thermal power plants. In this article, the authors consider the state and prospects of development of the world wind energy. The distribution of installed capacity of wind power plants by regions of the world is analyzed and the shares of countries in the total installed capacity are determined. The leading countries were identified as well as the reasons for the rapid growth of wind generation in these countries along with the measures of state support. The state and prospects of wind power development in Russia are considered, and it is also noted that the Russian Federation has significant potential in the field of wind power development, which makes it possible to make optimistic forecasts regarding the provision of electricity to remote areas of Russia. The technical electric power potential of wind energy is about 17.1 TW/year, which is an order of magnitude higher than the amount of electricity generated by all power plants in the country in 2018. The scientific increment is to identify the key problems facing the domestic wind power industry. Keywords: energy efficiency, energy saving, wind energy, wind power plants, Russian wind energy market JEL Ð¡lassifications: Q42, Q47, P28 DOI: https://doi.org/10.32479/ijeep.9938